Intrusion of teeth with class III furcation: a clinical, histologic and histometric study in dogs - Silva, Vanessa C. da [UNESP]; Cirelli, Carolina C. [UNESP]; Ribeiro, Fernando S. [UNESP]; Leite, Fabio R. M. [UNESP]; Benatti Neto, Carlos[UNESP]; Marcantonio, Rosemary Adriana Chierici [UNESP]; Cirelli, Joni Augusto [UNESP] (Wiley-Blackwell, 2008)
Aim: To assess orthodontic intrusion effects on periodontal tissues in dogs' pre-molars with class III furcations treated with open flap debridement (OFD) or with guided tissue regeneration (GTR) associated to bone autograft (BA).Material and Methods: Class III furcations were created in the pre-molars of seven mongrel dogs. After 75 days, teeth were randomly treated with OFD or GTR/BA. After 1 month, metallic crowns were assembled on pre-molars and connected apically to mini-implants by nickel-titanium springs. Teeth were randomly assigned to orthodontic intrusion (OFD+I and GTR/BA+I) groups or no movement (OFD and GTR/BA) groups. Dogs were sacrificed after 3 months of movement and 1 month retention.Results: All class III furcations were closed or reduced to class II or I in the intrusion groups, while 50% of the lesions in non-moved teeth remained unchanged. Intruded teeth presented higher probing depth and lower gingival marginal level than non-moved teeth (p < 0.01). Clinical attachment gain was reduced in the intrusion groups by the end of retention (p < 0.05). OFD+I presented smaller soft tissue area and larger bone tissue area than other groups (p < 0.05).Conclusion: Orthodontic intrusion with anchorage via mini-implants improved the healing of class III furcation defects after OFD in dogs. GTR/BA impaired those results.
Keywords: furcation defects; periodontal regeneration; surgical periodontal treatment; tooth intrusion